Removal of Cd2+ from aqueous solution using MgAICO3-layered double hydroxide / Nurul Izza Taib and Norzuyanti Mohd Aris - Taib, Nurul Izza; Mohd Aris, Norzuyanti (Research Management Institute (RMI), 2011)
Anion clay hydrotalcite MgAlCO3 with a Mg/Al molar ratio of 3:1 was synthesized by co-precipitation at room temperature and pressure. The physicochemical properties were evaluated using Powder X-Ray Diffraction (PXRD), Fourier Transform Infrared (FTIR) spectroscopy and Thermogravimetric Analysis (TGA). The efficacy of anion clay hydrotalcite in the removal of Cd2+ from aqueous solutions was investigated with respect to contact time, initial concentration, pH, adsorbent dosage and temperature. The Cd2+ removal increased with the increased in contact time, adsorbent dosage, pH and initial concentration. Adsorption decreases with increasing initial concentration and temperature, for which the latter is indicative of an exothermic process. The equilibrium adsorption capacity of MgAlCO3 was evaluated using linear Langmuir and Freundlich isotherms with respect to the separation factor, RL.